Amelioration of T Lymphocyte Subsets, Inflammatory Factors and Gastrointestinal Function by Traditional Chinese Medicine Rehabilitation Management in Postoperative Chemotherapy for Lung Cancer - Zou, Xiangni; Tang, Yuyang; Shi, Pei (Journal of Medical Biochemistry, 2025)
Background: To analyze the influence of Traditional Chinese Medicine (TCM)-characteristic rehabilitation management on T lymphocyte subsets, inflammatory response, and stress response during the postoperative chemotherapy of lung cancer (LC), aiming to provide a more reliable and valuable reference for future clinical treatment of LC. Methods: A total of 189 LC patients who were admitted to our hospital from July 2023 to June 2024 were enrolled in this research. Among them, 107 patients who did not receive TCM-characteristic rehabilitation management were regarded as the control group, while the other 82 patients who underwent such management were designated as the observation group. The levels of inflammatory factors and stress response markers before and after treatment in both groups were compared, includes hypersensitive-C reactive protein (hs-CRP), interleukin-6 (IL-6), superoxide dismutase (SOD), malondialdehyde (MDA), and glutathione peroxidase (GSH-Px). Additionally, the T lymphocyte subsets [CD3+, CD4+, CD8+, and natural killer (NK) cells] and gastrointestinal function were detected. Finally, we investigated the psychological status and sleep of the patients. Results: After the completion of treatment, it was observed that the levels of hs-CRP, MDA, and the proportion of CD8+ T lymphocyte subsets in the observation group were all significantly reduced compared with the control group (P<0.05). In contrast, the activities of SOD and GSH-Px, the proportions of CD3+ and CD4+ T lymphocyte subsets, as well as the activity of NK cells in the observation group were notably higher versus the control group (P<0.05). Moreover, the gastrointestinal function of the patients in the observation group exhibited a more favorable condition after treatment, with a remarkable reduction in the number of vomiting episodes and a significant shortening of the vomiting duration compared to the control group (P<0.05). Finally, we also found better psychological status and sleep quality in the observation group. Conclusion: TCM-characteristic rehabilitation management can effectively ameliorate inflammatory responses and stress injury in patients undergoing postoperative chemotherapy for LC, and enhance their immune and gastrointestinal functions.